COMMUNITY EMPOWERMENT BY STRENGTHENING THE TOURIST VILLAGE AND EDUCATION - Desi Tri Kurniawati; Sigit Pramono; Risca Fitri Ayuni; Isma Adila (Erudio Journal of Educational Innovation, 2021)
Tourism contributes much to the economy of Indonesia. As such, the government supports tourism development and encourages local governments to develop local potential, including rural tourism. Indonesia holds immense potential for rural tourism since the country has many villages with abundant resources for tourism. The development of tourist villages cannot be separated from rural tourism, an alternative for tourism in recent years amid the new trend of sustainable tourism. Tourists these days care much about environment conservation, community empowerment, and local culture. The development of tourist villages cannot be separated from the participation of the local community. However, problems arise in the development of tourist villages. Dusun Losawi also faces difficulties in developing itself as Kampung Dolanan. Although Kampung Dolanan has existed for four years, it has not benefited the local people. One solution to solve the problem is community empowerment through Community-Based Tourism (CBT). As a first step to identify the issues and formulate solutions in Kampung Dolanan, the community service team conducted field surveys and FGDs with Pokdarwis. The results were solutions in three main areas: (1) human resources—improvement of human resource quality through mindset training and comparative studies; (2) infrastructure sector—improvement through landmark construction, traditional toys provision, and land rental assistance; and (3) marketing communication—improvement through photography training, social media communication training, rural tourism marketing, and brand management. The activities carried out in the current program of Doktor Mengabdi were field surveys, FGDs, program proposals, mindset training, traditional toys provision, and preparation for other activities in September 2020.